Community Science as Adult Learning: Using Theory to Understand Volunteers’ Experiences - Lauren Vilen; Jill Zarestky (Adult Education Research Conference, 2024)
This study explores volunteer learning in an online community science program. Findings indicate alignment with self-directed and experiential learning theory, with implications for learner feedback and engagement.
Keywords: community science; adult STEM education; self-directed learning; experiential learning